ChemInform Abstract: A Facile Palladium‐Catalyzed Route to 2, 5, 7‐Trisubstituted Indoles. Issue 11 (February 2016) - Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia; Verdiglione, Rosanna
Abstract: Starting from compound (I) the synthesis of substituted indoles is achieved using different C—C or C—N bond forming reactions.